HUBUNGAN PAPARAN ASAP ROKOK TERHADAP KEJADIAN KETUBAN PECAH DINI DI PUSKESMAS RINGINARUM KABUPATEN KENDAL - Rozikhan Rozikhan; Titik Sapartinah; Ana Sundari (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2020)
Premature rupture of membranes is fluid discharge from the birth canal before the onset of labor. One risk factor is a decrease in ascorbic acid which results in abnormal structural growth. Preliminary survey results in Dr. H. Soewondo Kendal in 2013 there were 379 women giving birth with premature rupture of membranes. The purpose of this study was to determine the description of exposure to cigarette smoke in maternal with the occurrence of premature rupture of membranes in Dr. H. Soewondo Kendal. The design of this study is analytical research with cross-sectional study. The population was taken from parturient mother in RSUD Dr. H. Soewondo Kendal in May-June 2014 as many as 78 birth mothers consisting of 39 mothers with Premature rupture of membranes and 39 with no Premature rupture of membranes delivery. The sampling technique uses accidental sampling. Data collection using checklists and questionnaires. The results were obtained by 29 pregnant women (74.4%) with Premature rupture of membranes exposed to cigarette smoke and 10 people (29.4%) exposed to Premature rupture of membranes. While 15 respondents (34.1%) were not exposed to cigarette smoke and 24 (70.6%) were not exposed to cigarette smoke. Bivariate analysis results showed a p-value of 0.003 α-0.05. The conclusion is that there is a significant relationship between the incidence of Premature rupture of membranes in pregnant women with cigarette smoke exposure. Advice for midwives is to give advice to every pregnant woman to avoid cigarette smoke and provide quick and appropriate assistance to mothers who give birth with premature rupture of membranes so that it will reduce the danger of infection.